Analisis Kesiapan Guru Biologi dalam Mengimplementasikan Kurikulum Merdeka Belajar - Siahaan, Shalsabila; Khairuna, Khairuna (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The objective of this study is to explore the implementation of the Independent Learning Curriculum (Kurikulum Merdeka Belajar) and the challenges faced by teachers during its implementation. This research adopts a qualitative approach with a descriptive research design. The subjects of the study are the School Principal and Biology teachers at SMA Negeri 2 Percut Sei Tuan. Data collection involved observation, interviews, and documentation. Data analysis techniques included data reduction, data presentation, and drawing conclusions. Data validity was ensured through Technique Triangulation. The findings indicate that SMA Negeri 2 Percut Sei Tuan has implemented various aspects related to the Independent Learning Curriculum, one of which is the application of the Pancasila Student Profile through Project-Based Learning. Based on interviews, teachers encounter challenges in determining assessments that align with the intended learning objectives, especially in project-based learning scenarios. This confusion stems from the variety of assessment types such as presentations, projects, products, oral assessments, written assessments, and others. To address these issues, both the School Principal and teachers attend monthly training sessions as part of the Teacher Working Group (Kelompok Kerja Guru, KKG) to tackle problems and enhance teacher competence in teaching and learning activities.